Prevalence of High Bleeding Risk among Hospitalized Suspected NSTEMI Patients - Kesti Henri; Mäkinen Henna; Mattila Kalle; Jaakkola Samuli; Lintu Mikko; Porela Pekka (MDPI, 2022)
In recent years, guidelines for the management of acute coronary syndromes (ACS) have placed more emphasis on identifying patients at high bleeding risk (HBR). We set out to investigate the prevalence of HBR patients according to the Academic Research Consortium for High Bleeding Risk (ARC-HBR) criteria in hospitalized patients with suspected non-ST-segment elevation myocardial infarction (NSTEMI). Consecutive patients were retrospectively enrolled between January and June 2019 from the emergency department (ED) of a tertiary hospital. The discharge diagnosis and baseline data were manually collected using electronic patient records and database searches. Patients with non-cardiac diagnoses were excluded. Overall, 212 patients were included in the study. A total of 146 (68.9%) patients were diagnosed with NSTEMI (Type 1), 47 (22.2%) with unstable angina pectoris (UAP) and 19 (9.0%) with "other." HBR was detected in 47.6% (n = 101) of all patients. Common criteria for HBR among ACS patients were age (40.4%), chronic kidney disease (33.7%), and the use of oral anticoagulation medicines (20.2%). In conclusion, nearly half of the patients hospitalized for ACS fulfilled HBR criteria. According to contemporary guidelines, the management of HBR patients differs from that of non-HBR patients, and thus, a more comprehensive screening for HBR may be considered in clinical practice.